2017
DOI: 10.1111/aeq.12189
|View full text |Cite
|
Sign up to set email alerts
|

Between Rights and Realities: Human Rights Education for Immigrant and Refugee Youth in an Urban Public High School

Abstract: This article presents data from a two‐year ethnographic case study to explore how immigrant and refugee youth in the United States made sense of participation in a weekly human rights club after school. Three types of student responses to human rights education are exemplified through the profiles of students. The article offers new insights on studies of immigrant youth as well as possibilities that exist at the intersection of human rights education and anthropology of education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Other studies of students' ideas about protecting human rights point to a limited understanding of formal institutional procedures. Students in the United States (Russell, 2018;Torney & Brice, 1979) and Northern Ireland (Niens et al, 2006), for example, have displayed little understanding of the international frameworks or formal institutions responsible for human rights protections, although one study of U.S. immigrant students indicated that they had a general knowledge that nongovernmental organizations could play a role (Bajaj, Canlas, & Argenal, 2017). Students in India, Human Rights meanwhile, emphasized personal rather than institutional responsibility for human rights, through actions such as encouraging others not to engage in violations; reporting violations to those in a position of authority; educating others and spreading awareness of rights and their violation; and changing their own behaviors so that they did not violate others' rights (Bajaj, 2012a).…”
Section: Research On Students' Understanding Of Human Rightsmentioning
confidence: 99%
“…Other studies of students' ideas about protecting human rights point to a limited understanding of formal institutional procedures. Students in the United States (Russell, 2018;Torney & Brice, 1979) and Northern Ireland (Niens et al, 2006), for example, have displayed little understanding of the international frameworks or formal institutions responsible for human rights protections, although one study of U.S. immigrant students indicated that they had a general knowledge that nongovernmental organizations could play a role (Bajaj, Canlas, & Argenal, 2017). Students in India, Human Rights meanwhile, emphasized personal rather than institutional responsibility for human rights, through actions such as encouraging others not to engage in violations; reporting violations to those in a position of authority; educating others and spreading awareness of rights and their violation; and changing their own behaviors so that they did not violate others' rights (Bajaj, 2012a).…”
Section: Research On Students' Understanding Of Human Rightsmentioning
confidence: 99%
“…At the same time, there might be more lucid examples of neighbours, so that the importance of social support for refugees can be understood. In one of the studies, lack of communication with neighbors had been associated with depression [11,12].…”
Section: Educationmentioning
confidence: 99%
“…In contrast, some schools uniquely cater to 'newcomer' student populations, developing inclusive practices and responsive curriculum. In recent work, particularly a set of studies with the Internationals Network for Public Schools, researchers find that schools designed to take into consideration the sociocultural needs of migrant populations correlate with positive social and academic outcomes for students and their families (Bajaj, Canlas and Argenal 2017;Bajaj and Bartlett 2017;Mendenhall, Bartlett and Ghaffar-Kucher 2017). These studies demonstrate that social belonging, a component of sociocultural integration, coupled with high quality education can overcome negative effects of segregation.…”
Section: Theories Of Integration Are Widely Critiqued Amongst Educatimentioning
confidence: 99%